Production of Phosphorescent Coatings on 6082 Aluminum Using Sr0.95Eu0.02Dy0.03Al2O4-δ Powder and Plasma Electrolytic Oxidation - Auzins, Krisjanis; Zolotarjovs, Aleksejs; Bite, Ivita; Laganovska, Katrina; Vitola, Virginija; Smits, Krisjanis; Millers, Donats (MDPI AG, 2019)
In this study, a new approach for producing phosphorescent aluminum coatings was studied. Using the plasma electrolytic oxidation (PEO) process, a porous oxide coating was produced on the Al6082 aluminum alloy substrate. Afterwards, activated strontium aluminate (SrAl2O4: Eu2+, Dy3+) powder was filled into the cavities and pores of the PEO coating, which resulted in a surface that exhibits long-lasting luminescence. The structural and optical properties were studied using XRD, SEM, and photoluminescence measurements. It was found that the treatment time affects the morphology of the coating, which influences the amount of strontium aluminate powder that can be incorporated into the coating and the resulting afterglow intensity.
Keywords: Aluminum 6082; Luminescent coatings; Phosphorescence; Plasma electrolytic oxidation (PEO); Research Subject Categories::NATURAL SCIENCES:Physics